Prospective Teachers. Conceptions about Mathematics and its Teaching and Learning - Marcos Augusto Zapata; Lorenzo Jesús Blanco; Luis Carlos Contreras (Revista Electrónica Interuniversitaria de Formación del Profesorado)
Teachers' thinking and their activity in class constitute a means of understanding teaching. The interpretation of this thinking is one of the bases for designing education proposals in centres of initial and continuing teacher education. The work presented describes a study conducted with prospective teachers specializing in Mathematics and Physics in the Education Faculty of the University of Piura, Peru. The objective of the study was to identify their conceptions about mathematics and its teaching and learning.